2010
DOI: 10.1016/j.jcp.2010.05.040
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and robust numerical algorithm for estimating parameters in Turing systems

Abstract: a b s t r a c tWe present a new algorithm for estimating parameters in reaction-diffusion systems that display pattern formation via the mechanism of diffusion-driven instability. A Modified Discrete Optimal Control Algorithm (MDOCA) is illustrated with the Schnakenberg and Gierer-Meinhardt reaction-diffusion systems using PDE constrained optimization techniques. The MDOCA algorithm is a modification of a standard variable step gradient algorithm that yields a huge saving in computational cost. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The reaction kinetics (5.2) are known as the activator-depleted substrate model [Lefever and Prigogine, 1968]. They have been used widely in the modelling of biological pattern formation phenomena and there has been progress in the analysis of RDSs on fixed and growing domains equipped with the kinetics (5.2) at the continuous level [Kolokolnikov et al, 2008;Venkataraman, 2011; and in the analysis of numerical methods to approximate the equations [Garvie et al, 2010;.…”
Section: Numerical Experiments With Artificial Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction kinetics (5.2) are known as the activator-depleted substrate model [Lefever and Prigogine, 1968]. They have been used widely in the modelling of biological pattern formation phenomena and there has been progress in the analysis of RDSs on fixed and growing domains equipped with the kinetics (5.2) at the continuous level [Kolokolnikov et al, 2008;Venkataraman, 2011; and in the analysis of numerical methods to approximate the equations [Garvie et al, 2010;.…”
Section: Numerical Experiments With Artificial Datamentioning
confidence: 99%
“…Parameter identification for semilinear reaction-diffusion systems has received some attention in the literature Friedman and Reitich, 1992;Garvie et al, 2010;Jiang and Zhang, 2000] and there have also been some studies focussed on optimal control and related inverse problems in the context of geometric evolution equations and free boundary problems [Deckelnick et al, 2009[Deckelnick et al, , 2011Haußer et al, 2010Haußer et al, , 2012. There has also been some work on parameter estimation in models of cell motility.…”
Section: Introductionmentioning
confidence: 99%
“…In some bio-medical applications the parameters could also be spatially dependent functions, like in [38,39] where the birth rate of proliferative cells in colon cancer is estimated. Recent studies on parameter estimation in the context of biological pattern formation ( [40], [41], [42]) have concentrated on development of the methodology, including demonstration of well-posedness and efficiency of solution methods. Here we apply parameter estimation methods using gradient descent algorithms in order to analyse the behaviour of our model of electrochemical pattern formation in different parameter regimes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that one key application of such optimal control formulations is to find solutions to pattern formation problems [10,11], and so it is natural to explore this particular application here.…”
mentioning
confidence: 99%
“…PDEconstrained optimization problems of similar form have been considered in the literature, such as in [10,11].…”
mentioning
confidence: 99%